Surtain Herbicide Evaluation in Corn - Patrick W. Geier (Kansas Agricultural Experiment Station Research Reports, 2024)
This study investigated the use of Surtain herbicide compared to commercial standards for efficacy in corn. All herbicides evaluated provided good control of kochia, Russian thistle, and green foxtail. Surtain and Trivolt each controlled common sunflower and Johnsongrass 90% or more, whereas only Surtain controlled Palmer amaranth more than 80% throughout the season. Relative to the untreated control, grain yields were greatest when Surtain was applied preemergence at the higher rate, as an early postemergence treatment, or when it was followed by a postemergence treatment.
Keywords: Residual herbicides; multiple modes of action